Process Safety in Coal Mining - Du, Feng; Zhou, Aitao; Li, Bo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Coal is an important natural resource. Improving the safety levels of the coal mining process while ensuring that coal production is at an acceptable level are problems to which we must attribute great importance. This reprint focuses on the safety of coal mine production, including the latest work from leading researchers. It discusses and studies the progress of research on safety in theory, experiments and simulation. The content covers the safety of coal mine-related fields, including mine ventilation, fire and explosion prevention, gas drainage, coal dust prevention, safety equipment, and other aspects of safety technology research. Despite the interdisciplinary nature of the different studies, the common theme of security is closely linked to the different studies in this period.